Flexible hybrid coatings with efficient antioxidation properties. (December 2016) - Bossi, Elisabetta; Tana, Francesca; Punta, Carlo; Cigada, Alberto; De Nardo, Luigi
Highlights: Hybrids flexible coatings for food packaging. Efficient incorporation and release of α-tocopherol. Antioxidant efficacy demonstrated up to four months. Abstract: In this work, the feasibility of a transparent sol gel coating on polyamide-polyethylene (PA/PE) substrate with antioxidant properties as active food packaging was investigated. Stable water-based silicon alkoxide formulations, containing lipophilic vitamin E as natural antioxidant, were obtained adding ascorbic acid as catalyst. Comparative blank sols were prepared without antioxidant guest molecules. The sol formulations of tetraethyl orthosilicate and a mixture of alcoxysilane containing organic moieties as phenyl and methyl group were stable and easy to process via dip coating on Polyamide/Polyethylene substrates. Organic functionalities were essential to incorporate the lipophilic guests and to achieve an optimal adhesion on the polymeric substrate. The presence of stable coating was evaluated through Electron Microscopy and Optical Emission Spectroscopy analyses, while the surface roughness and optical absorption were measured by noncontact laser profilometry and by UV/vis spectra. The loaded antioxidant amount was estimated right after the coating deposition by spectroscopic UV measurements in ethanol, as its subsequent release within 14 days. The estimated antioxidant release was 10% and 40% of the loaded amount for the hydrochloric-sol and the ascorbic acid catalysed sol, respectively. The antioxidant efficacy of coatings was evaluated through the Ferric Reducing Antioxidant Power (FRAP) assay showing a significant difference in antioxidant efficacy between the vitamin E containing sols and their blank ones. Those results were confirmed by FRAP analysis even four months after the deposition.